ERNEST HEMINGWAYâS A CLEAN, WELL-LIGHTED PLACE : AN ANALYSIS ON ITS STRUCTURE AS A MEANS OF COMMUNICATION WITH THE READER - ., Kustinah (MAGISTRA, 2016)
This writing aims at finding the mental evidences from a short story written by ErnestHemingway entitled A Clean, Well-Lighted Place. The writer of this paper wants to show readers thatreading a literary work means a communication process between the text and its readers. Reading is anactivity that is guided by the text, this must be processed by the reader, who is then, in turn, affected by whathe has processed.The interpretation as the result of one reading-act; arises from the structure of interpersonal experience.Theoretically speaking, literary works are believed as a portrait of humanâs experience. So, in the discussion,the writer of this article will guide readers how the short story communicates the values as our mirror to viewourselves and conclude the universality of the text.A successful relationship between the text and the reader can only come about through changes in thereaderâs projections. Thus the text provokes continually changing views in the reader. The imbalance betwentext and reader, however, is undefined, and it is this very indeterminacy that increases the variety of communicationpossible. If this possibility is fulfilled, and if the communication betwen text and reader is to be successful,clearly, the readerâs activity must be controlled in some way by the text.The conclusion of this writing will sum up the previous analysis of the short story; and yet showreaders that the asymmetry between text and reader stimulates a constitutive activity on the part of the reader.This is given a specific structure by the blanks and the negations arising out of the text, and the structurecontrols the process of interaction.Key-words : literary text, comunication process